Suggestions to close the gap in nursing education: Nursing students' perspectives - Saifan, Ahmad; Abu Safieh, Haneen; Milbes, Ruba; Shibly, Rawan (International Journal of Advanced Nursing Studies, 2015)
Background: The nursing profession is composed of two main parts: the theoretical part, which reflects the knowledge that is received in the classroom; and the practical part, which focuses on improving students’ skills in the clinical area. The literature shows that there is a disconnect between these two parts.Objectives: This study aimed to identify suggestions and interventions to explore students’ perceptions about the theory-practice gap in nursing education.Methods: An explorative qualitative design with individual, face-to-face, semi-structured interviews with 30 nursing students (in the second, third and fourth year of their BSc program) who took at least two clinical courses.Results: The students raised several ideas and suggestions to close the theory-practice gap in nursing education grouped under five major themes: open channels between theory and practice teachers; students need to be supported more; increasing competency of clinical instructors; using different methods of education; and preparing and improving the clinical laboratories.Conclusion: The qualitative design used in this study provided deep and rich novel data about the theory-practice gaps in nursing education in Jordan. This subject was broached for the first time in Jordan. The information from this study could be useful for undergraduate students, nursing schools, nursing teachers and other healthcare stakeholders in Jordan.